Biocompatibility of composite resins - Sayed Mostafa Mousavinasab (Wolters Kluwer Medknow Publications, 2011)
Dental materials that are used in dentistry should be harmless to oral tissues, so they should not contain any leachable toxic and diffusible substances that can cause some side effects. Reports about probable biologic hazards, in relation to dental resins, have increased interest to this topic in dentists. The present paper reviews the articles published about biocompatibility of resin-restorative materials specially resin composites and monomers which are mainly based on Bis-GMA and concerns about their degradation and substances which may be segregated into oral cavity.